Virtual Vortex: The Marketing Mix and its Effect on Digital Consumer Behavior for Non-Durable - Venkatesan, Chandralekha; Rajeswari (Jurnal Internasional Penelitian Bisnis Terapan, 2025)
This research aims to delve into the influence of the marketing mix, including the 4Ps (product, price, place, and promotion), along with supplementary elements such as visual representation and aesthetics, on consumer purchase intentions in an online environment. Additionally, it investigates which components of the marketing mix and mediating factors play the most pivotal roles in shaping consumer behavior towards online purchases of non-durable goods. The research framework was designed by incorporating the theory of the marketing mix. This study employed a descriptive analysis approach on a sample of 249 respondents, selected through convenience sampling. Data analysis was performed using IBM AMOS software, utilizing PLS-SEM to investigate the relationships between the marketing mix components, visual representation, aesthetics, and purchase intentions for non-durable goods. The study identified consumer attitudes towards online purchasing behavior. The results reveal that visual representation and aesthetics exert the most significant influence on purchase intentions among online consumers.